Training according to sensory information through visual observation in improving some biomechanical indicators of hammer throwing for Applicants - Ebadi Abid AL-Khafaji, Mohammed (International Journal of Psychosocial Rehabilitation, 2023)
Feedback with a sense of movement is the basis for the picture of correct performance in hammer throwing. This leads the thrower to control the movements that occur below perception, which allows him to review other aspects of movement so that the feedback information is consistent with the picture of motor performance, which allows the thrower to perform better in situations. Competition, and this problem the researcher wanted to find solutions to through visual monitoring of the shooter’s performance and reviewing it by the player and coach to identify the exact defect in performance and avoid it through repeated practices accompanied by this type of feedback. The research may require measuring some mechanical variables to demonstrate the effectiveness of using feedback through repeated and immediate visual review in correcting them. The research was applied to a sample of advanced Iraqi hammer throwers three times a week for a period of (6) weeks. Among the results of the research was the development of the instantaneous momentum at the moment of throwing, and the development of The resulting acceleration (vertical and tangential) at the moment the hammer is fired, the differences in the amount of movement between the throwing position and the final throw decrease, and the final achievement improves.